The Role of the Energy Sector in the Iranian Economy - Chuvakhina, Larisa G.; Nasirbeik, Anahita; Yarygina, Irina Z.; Ustinova, Olga E.; Terskaya, Galina A. (International Journal of Energy Economics and Policy, 2023)
This paper is devoted to analyzing the processes that took place in the energy sector of Iran for the period from 2004 to 2021. It is emphasized that for the sustainable development of the country's economy, a reliable, long-term, and economically acceptable supply of various types of energy in their optimal combination is necessary. Despite the territory of Iran having an extremely high potential for the development of non-traditional energy, the analysis shows that the development of the Iranian economy is mainly based on oil revenues. In the context of the growing crisis in the global economy, an increase in demand for oil and oil products, oil accents in energy diplomacy began to intensify, which allows us to speak about the actualization of the problems of developing the oil and gas sector of Iran and shifting the focus towards traditional energy sources. Nevertheless, to achieve sustainable development, along with the possession of a resource base, the availability of modern equipment and technologies, and dominance in the market for products that foreign partners are interested in acquiring are necessary. It is concluded that Iran is vulnerable to geo-economic risks in the current conditions of the development of the world economy.